Efficiency improvement of photovolatic by using maximum power point tracking based on a new fuzzy logic controller - Effendy, Machmud; Mardiyah, Nuralif; Hidayat, Khusnul (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2018)
Maximum power point tracking (MPPT) is a technique to maximize the power output of photovoltaic (PV). Therefore, to achieve higher PV efficiency, the development of MPPT control algorithm is necessary. Recently, it was revealed that fuzzy logic controller (FLC) is better than other control algorithms and is possible toe developed. This study fabricated and implemented MPPT based on the proposed a new FLC. Input Calculator (IC) via sensors reads current and voltage of PV and generates the comparison of voltage and current of PV, then IC output becomes fuzzy algorithm input. Fuzzy algorithm produces duty cycle that drives synchronous buck converter. The result showed that MPPT system with proposed FLC method has 99.1% efficiency while MPPT system with P&O method has 95.5% efficiency. From the obtained result, it can be concluded that the MPPT based on the proposed FLC can increase the overall efficiency of the system to 99.3%.